Biological and molecular characterisation of Bidens mosaic virus supports its assignment as a member of a distinct species in the genus Potyvirus - Sanches, Marcio Martinello [UNESP]; Marchi, Bruno Rositto de [UNESP]; Spadotti, David Marques [UNESP]; Nozaki, Denise Nakada [UNESP]; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Springer, 2014)
The complete nucleotide (nt) sequence of Bidens mosaic virus (BiMV) isolate SP01 was determined and shown to consist of 9,557 nt. Since it shared highest identities in the nt sequence of the whole genome (66-73 %) and in the aa sequence of the polyprotein (60-76 %) with viruses of the potato virus Y subgroup, it was compared with them genetically and biologically. Phylogenetic analysis showed that the closest relative of BiMV is sunflower chlorotic mottle virus, from which it, however, differed significantly in various respects. These results indicate that BiMV should represent a distinct species in the genus Potyvirus.